Research of rotary transformer monitoring and regulation system of biogas reactor operation - Babak, D. (Energy and Automation, 2026)
This article is devoted to improving the method of transmitting electrical energy to rotating components of electromechanical systems, particularly in explosive or chemically aggressive environments. The objective of the study is to justify the use of a transformer with a rotating secondary winding for contactless power transmission to the rotating part of a submersible multifunctional electromechanical transducer (PMET) as part of a system for monitoring and regulating the operating mode of a biogas reactor. In the developed system, the transformer structure is implemented as a rotating transformer (RT) with axially arranged windings: the primary winding is rigidly fixed on a stationary steel core, and the secondary winding is mounted on the PEMP. To evaluate the dynamic properties of the RT, a series of measurements was conducted while varying the frequency of the input P-shaped signal from 1.5 to 7 kHz. The RT power supply circuit is based on an IR2153 PWM driver that controls two MOSFET transistors. Analysis of the electromagnetic field and the distribution patterns of magnetic induction was performed in the Comsol Multiphysics software environment. The choice of a 2 kHz supply frequency was confirmed by the achieved power and efficiency values. The proposed OT is distinguished by its topological features and operating mode in measurement cycles. To eliminate the influence of the sensor power supply system on the thermal profile, a special algorithm for the OT’s operation was developed. The resulting prototype demonstrates an average efficiency of 75% in the output power range of 300–500 mW. The proposed topology makes it possible to increase the power of the operational technology system without compromising its size, cost, or performance. Future research directions include ensuring the electromagnetic compatibility of the monitoring and control system and investigating its impact on the substrate of the biogas reactor. Recieved: 20.01.2026. Recieved: 23.03.2026. Accepted: 17.04.2026.